1999
DOI: 10.1038/sj.mp.4000510
|View full text |Cite
|
Sign up to set email alerts
|

Mapping susceptibility loci in attention deficit hyperactivity disorder: preferential transmission of parental alleles at DAT1, DBH and DRD5 to affected children

Abstract: Attention deficit hyperactivity disorder (ADHD) is a common disorder of childhood characterized by inattention, excessive motor activity, impulsivity, and distractibility. It is associated with serious disability in children, adolescents and adults. 1 The etiology of the disorder is unknown, but it has a strong genetic component. Pharmacological and biochemical studies have suggested that dopaminergic and noradrenergic systems are involved. 2 Using a sample of affected children and their parents we have found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
285
8
12

Year Published

2000
2000
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 348 publications
(324 citation statements)
references
References 24 publications
16
285
8
12
Order By: Relevance
“…Cook et al (1995) reported an association between the 480bp DAT1 allele, one of the common alleles of a 40bp repeat situated in the 3 Ј untranslated region of the DAT1 gene which maps to 5p15.3 and ADHD. Since then, this finding has been replicated by our group (Gill et al 1997;Daly et al 1999 (in a UK sample), but not by others (Asherson et al 1998;Palmer et al 1999;Holmes et al 2000;and Roman et al 2001). DRD4, the gene encoding the dopamine D4 receptor, has also attracted interest as a candidate gene.…”
mentioning
confidence: 52%
See 4 more Smart Citations
“…Cook et al (1995) reported an association between the 480bp DAT1 allele, one of the common alleles of a 40bp repeat situated in the 3 Ј untranslated region of the DAT1 gene which maps to 5p15.3 and ADHD. Since then, this finding has been replicated by our group (Gill et al 1997;Daly et al 1999 (in a UK sample), but not by others (Asherson et al 1998;Palmer et al 1999;Holmes et al 2000;and Roman et al 2001). DRD4, the gene encoding the dopamine D4 receptor, has also attracted interest as a candidate gene.…”
mentioning
confidence: 52%
“…Approximately 80% of the children in this study with ADHD also met diagnostic criteria for other disorders such as Oppositional Defiant Disorder and Conduct Disorder. Details of diagnosis and clinical criteria can be found in Daly et al (1999). Briefly, consensus diagnoses were made according to DSM-IV ADHD or UADD, either with or without comorbidity.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations